Utilization of Inconventional Feedstuffs for Animal Production - Mathius, I W; Sinurat, A P (Indonesian Bulletin of Animal and Veterinary Sciences, 2001)
In the recent past, the increasing cost of imported feed ingredients, known as the main components of completed ration, caused the bankrupt of the intensive poultry industry. On the other hand, negative affect was faced by ruminant animal due to the potential land used for agriculture has been swidden/shifted to non-agricultural function, resulting in a shortage of feed sources, availability and supply for ruminant animal. Consequently, the animal productivity is low. There is ,therefore a need to look for cheaper alternative sources of feedstuffs has to be given in order to optimize the productivity of animal utilizing available feed in this country. A number of investigations have been done in order to overcome the feed availability problem, including the potential of crop by-product as a part of concentrate component. Although, crop by-product is   always generally related to cheaper feedstuff, there are several matters need to be considered. Those factors are the continuation of crop by-product availability, the nutrient content of crop by-products, the possibility of any limiting factors, such as the existence of toxic constituents as well as the processing needed before feeding to the animal. Experiment results on utilization of several crop by- products, such as rice bran, cassava leaves, coconut meal, palm oil cake, cocoa pod husks, tofu residue, shrimp (Penaeus Sp) meal, banana steam and rami (Haramaj Sp) leaves  in feeding ruminant animal (cattle and sheep) and non-rumiants animal (local and imported poultry as well as duck) will be reviewed in this paper.   Key words: Inconventional feedstuffs, crop by-product, animal production